2019
DOI: 10.1002/bab.1733
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid‐responsive AabHLH1 positively regulates artemisinin biosynthesis in Artemisia annua

Abstract: Artemisia annua is the only natural source of the sesquiterpenoid artemisinin, which is widely used to treat malaria. The phytohormone jasmonic acid (JA) can significantly promote artemisinin biosynthesis in A. annua. AabHLH1 can bind and activate artemisinin biosynthetic genes, such as AaADS and AaCYP71AV1. In this study, we proved that AabHLH1 was responsive to MeJA treatment and highly expressed in glandular trichome-enriched tissues, and that its expression profile was similar to that of AaADS. Yeast two-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The transcript levels of TPS genes were regulated by a number of different TFs. So far, six TF families in plants associated with terpenoid metabolism have been identified, including AP2/ERF [25,26,32,33], bHLH [31], MYB [27], NAC [28], WRKY [29], and bZIP [30]. Their gene IDs are summarized in Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcript levels of TPS genes were regulated by a number of different TFs. So far, six TF families in plants associated with terpenoid metabolism have been identified, including AP2/ERF [25,26,32,33], bHLH [31], MYB [27], NAC [28], WRKY [29], and bZIP [30]. Their gene IDs are summarized in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al found that AtMYC2 combines multiple plant hormone signals in the transcriptional regulation of sesquiterpene biosynthesis and activates the production of ( E )-β-caryophyllene [31]. AaERF1 and AaERF2 positively regulate the expression level of ADS and CYP71AV1 , leading to the accumulation of artemisinin [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…JA also promotes degradation of the AaJAZ8 repressor, a negative regulator of TCP14-ORA complex formation. Li et al ( 2019 ) showed that JA has a positive impact on artemisinin biosynthesis due to its stimulatory effect on AaBHLH , which in turn induces artemisinin biosynthetic genes, such as ADS and CYP71AV1. These results suggest that JA biosynthetic genes such as AaAOC and AaOPR3 and JA responsive transcription factors such as AaBHLH, ERF1 and ORA have potential for creating transgenic varieties with increased artemisinin content.…”
Section: Artemisinin Enhancement Strategiesmentioning
confidence: 99%
“…Using transient assays in both Nicotiana tabacum leaves or Actinidia arguta fruits and stable transformation in Arabidopsis, Wang et al (2019) demonstrated that co-expression of AcMYB123 and AcbHLH42 is a prerequisite for anthocyanin production by activating transcription of AcF3GT1 and AcANS or their homologous genes. Li L. et al (2019) found that AabHLH1 interacted with AaMYB3 to regulate the accumulation of procyanidine. In addition, DhMYB2 interacted with DhbHLH1 to regulate anthocyanin production in Dendrobium hybrid petals .…”
Section: Regulatory Mechanism Of Bhlhs Involved In Transcriptional Activationmentioning
confidence: 99%